Therapeutic Suggestions During General Anesthesia Reduce Postoperative Nausea and Vomiting in High-Risk Patients – A Post hoc Analysis of a Randomized Controlled Trial - Nowak, Hartmuth; Wolf, Alexander; Rahmel, Tim; Oprea, Guenther; Grause, Lisa; Moeller, Manuela; Gyarmati, Katharina; Mittler, Corinna; Zagler, Alexandra; Lutz, Katrin; Loeser, Johannes; Saller, Thomas; et al. (Frontiers in Psychology, 2022)
Postoperative nausea and vomiting (PONV) are one of the most adverse events after general anesthesia, a distressing experience, and pose a risk to the patient. Despite advances in drug prophylaxis and PONV treatment, the incidence remains high and additional non-pharmacological treatments are needed. In this post hoc analysis of a recently published double-blind multicenter randomized controlled trial on the efficacy of intraoperative therapeutic suggestions on postoperative opioid dosage, we analyzed the effects of intraoperative therapeutic suggestions on PONV. We focus on patients with a high risk of PONV (Apfel risk score of 3-4) and distinguished early (first 2 postoperative hours) and delayed PONV (2-24h). A total of 385 patients with a moderate or high risk for PONV were included. The incidence of early and delayed PONV was reduced (22.7% to 18.3% and 29.9% to 24.1%, respectively), without statistical significance, whereas in high-risk patients (n=180) their incidence was nearly halved, 17.2% vs. 31.2% (p=0.030) and 20.7% vs. 34.4% (p=0.040), corresponding to a number needed to treat of 7 to avoid PONV. In addition, there was a significant reduction in PONV severity. In a multivariate logistic regression model, assignment to the control group (OR 2.2; 95% CI: 1.1-4.8) was identified as an independent predictor of the occurrence of early PONV. Our results indicate that intraoperative therapeutic suggestions can significantly reduce the incidence of PONV in high-risk patients. This encourages the expansion of therapeutic suggestions under general anesthesia, which are inexpensive and virtually free of side effects. This study was registered in the German Clinical Trials Register (registration number: DRKS00013800, https://drks.de)